Subsurface soil inorganic carbon gains offset half of surface losses in China’s upland croplands over the last four decades - Andong Cai; Tianfu Han; Zhenghu Zhou; Kailou Liu; Xinpeng Xu; Pete Smith; Qingzhu Gao; Yue Li; Minggang Xu (Proceedings of the National Academy of Sciences, 2026)
Soil inorganic carbon (SIC) constitutes half of the terrestrial carbon pool and exerts a profound influence on global carbon cycling and ecosystem multifunctionality. Contrary to the view of millennial-scale stability, SIC in cropland are undergoing rapid changes due to intense anthropogenic disturbances. However, the direction, magnitude, and drivers of SIC changes over recent decades remain poorly quantified, especially in entire soil profile. Here, we quantified changes in SIC across a 1-m soil profile across China’s upland croplands at 204 matched sites (4,305 soil profiles) in 1980s and 2023, relocated using legacy site descriptions and field verification. Over the past four decades, the mean of surface SIC density (0 to 40 cm) depleted by 0.68 kg m −2 , primarily associated with increased precipitation and soil acidification, whereas subsurface SIC density (40 to 100 cm) increased by 0.49 kg m −2 , attributed to carbon inputs and an increase in soil pH. Subsurface SIC accumulation amounted to 0.48 0.39 0.58 Pg, offsetting 44% surface losses within the upper 1 m soil profile. Importantly, this offset reflects vertical redistribution of SIC rather than net carbon sequestration at the ecosystem scale. These findings highlight the need to incorporate depth-resolved SIC dynamics into terrestrial carbon accounting and climate projections.